2012
DOI: 10.1016/j.whi.2011.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Risk Behaviors among African-American and Hispanic Women in Five Counties in the Southeastern United States: 2008–2009

Abstract: Purpose We examined sexual risk behaviors and unrecognized HIV infection among heterosexually active African American (AA) and Hispanic women. Methods Women not previously diagnosed with HIV infection were recruited in rural counties in North Carolina (AA) and Alabama (AA), and an urban county in southern Florida (Hispanic) using multiple methods. They completed a computer-administered questionnaire and were tested for HIV infection. Results Between October 2008 and September 2009, 1527 women (1013 AA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 42 publications
5
34
2
Order By: Relevance
“…However, several behavioral studies and clinical trial reports have shown that women also engage in unprotected receptive anal intercourse (RAI), with the highest rates of RAI being found among female sex workers and patients at sexually transmitted infection clinics (1)(2)(3)(4)(5)(6)(7)(8)(9). In addition, a recent metaanalysis demonstrated that the estimated per-act human immunodeficiency (HIV) transmission risk (per 10,000 exposures) for RAI is 138, compared to 11, 8, and 4 for insertive anal intercourse, receptive penile-vaginal intercourse, and insertive penile-vaginal intercourse, respectively (10).…”
mentioning
confidence: 99%
“…However, several behavioral studies and clinical trial reports have shown that women also engage in unprotected receptive anal intercourse (RAI), with the highest rates of RAI being found among female sex workers and patients at sexually transmitted infection clinics (1)(2)(3)(4)(5)(6)(7)(8)(9). In addition, a recent metaanalysis demonstrated that the estimated per-act human immunodeficiency (HIV) transmission risk (per 10,000 exposures) for RAI is 138, compared to 11, 8, and 4 for insertive anal intercourse, receptive penile-vaginal intercourse, and insertive penile-vaginal intercourse, respectively (10).…”
mentioning
confidence: 99%
“…In the previously mentioned Murray et al study, social factors involving parental and societal influence seemed to shape women's attitudes regarding their relationships and acceptance of the possibility of pregnancy (2013). Other empirical findings reveal that social determinants including financial adversity, relationship status, gender roles, and family or household structure have the potential to manipulate and distinguish the emotional and relational factors that underlie AAWs reproductive and sexual health (McLellan-Lemal et al, 2012;Sharpe et al, 2012).…”
Section: Sexual Healthmentioning
confidence: 99%
“…The identification of patterns of sexual risk behaviors and development of interventions to reduce or eliminate those behaviors has long since been the focus of research studies examining the sexual and reproductive health of AAW (McLellan-Lemal et al, 2012;Neblett et al, 2011;Reid et al, 2014). With heterosexual contact being attributed to most new HIV infections and other STIs in AAW, behavioral factors frequently identified in the examination of sexual risk for these women include: inconsistent condom use, having multiple or concurrent sexual partners, and the use of illicit drugs (Centers for Disease Control and Prevention, 2014b;McLellan-Lemal et al, 2013;Perkins, Stennis, Taylor Spriggs, Kwegyir-Afful, & Prather, 2014).…”
Section: Sexual Risk Behaviormentioning
confidence: 99%
See 2 more Smart Citations